Management of the system of vocational adaptation of students in the training process in a vocational school - Bachiieva, L. (Problems of Engineer-Pedagogical Education, 2019)
The article presents the results of theoretical research on the development of a model of management of the system of students’ professional adaptation on the basis of management functions (analytical, planning, organizational, motivational, and controlling). The analytical function involves analysis of the information gathered during the collection of information about the individual characteristics of students and will allow determining their abilities and ways to improve the quality of this process. The function of planning involves setting the main goals and objectives, justifying the methodological approaches and principles of managing the professional adaptation of students in the process of vocational training in a vocational education institution. The function of organization and motivation in the model considered is related to the implementation of the complex organizational and pedagogical conditions of management, which ensures the effectiveness of the process of professional adaptation of students. The control function involves monitoring and diagnosing the state of the process of professional adaptation for interim results. The developed model has a system for placing elements and obeying the patterns. All elements of the model are in the order of dominance: from top to bottom. To implement the model, the following programs are presented: "Program of pedagogical and socialprofessional diagnostics of students' personality" and "Pedagogical support of students in the process of professional adaptation". The programs implement a complex of organizational and pedagogical conditions for the professional adaptation of students: conducting pedagogical diagnosis of the students' professional qualities in order to gradually track their personal growth; cultivating traditions of an educational establishment in the process of students’ training; providing students with pedagogical support in overcoming obstacles and difficulties in the process of entering the profession.